Handbook of SAARC - "Singh, Sudhir Kumar. (ed.)" (New Delhi, 2012)
Thus, SAARC itself dedicated to economic, technological, social, and cultural development emphasizing collective self-reliance. Due to variety of prevailing problems, it could not come up to the expectations but it has created an excellent infrastructure for the regional cooperation. Since 1985, it has done a commendable job for the promotion of regional cooperation. The book gives a comprehensive coverage to all the documents related to SAARC since its inception to last Summit held at Thimpu (2010). It will be extremely useful for all concerned and the supporters of regional cooperation in general and students pursuing SAARC in particular.
Keywords: South Asian Association for Regional Cooperation